Novel Cooling Device Enhances Autonomic Nervous System Recovery from Live Fire Training: A Pilot Study - Edmonds, Rohan C.; Wilkinson, Andrea F.; Fehling, Patricia C. (International Journal of Innovative Research in Medical Science, 2017)
Background: The occupation of firefighting is strenuous and dangerous. Firefighters perform demanding work while wearing heavy, insulative PPE. Thus, heat stress is a constant concern. The fire service has protocols to allow for rest, rehydration, and cooling. However, finding cooling techniques that are effective and convenient remains a challenge for many departments. The aim of this study was to determine the effectiveness of a novel cooling device during firefighting training drills. Methods: Firefighters reported to REHAB during a day-long training class, and were randomly assigned to wear the dhamaSPORT cooling band in cooling mode or off mode. During the required REHAB, heart rate and perceived measures of comfort were assessed on 41 volunteer firefighters. Additionally, a sub-group of 12 firefighters wore a continuous heart rate monitoring system to assess autonomic balance changes during cooling vs. control. Results: There was a significant reduction in the perceptual measures when wearing the cooling band, and there is enhanced improvement of the autonomic nervous system balance evidenced by a decrease in RMSSD, indicating a decrease in parasympathetic tone following firefighting. However, this reduction was less in the cooling group. The results of this study indicate that the wearable cooling band improves perceptual measures and hastens autonomic nervous system recovery. Additional testing is warranted to assess the long-term impact on firefighters’ health and recovery from firefighting duties, training, or actual fire calls.